Millennium Challenges for Development and Faith Institutions - Marshall, Katherine; Marsh, Richard (Washington, DC: World Bank, 2013)
The dialogue initiated at Lambeth -- continued at a second meeting of faith and development leaders in November 1999 and then at the third meeting in Canterbury, on which this booklet is based -- has endeavored to bridge these gaps. Organizers of the Canterbury meeting documented some case studies of partnerships between faith and development institutions, summarized in this booklet, as background for the gathering. These cases, many of which had previously been only partially documented, reveal a diversity of experience across countries, regions, and sectors on which to build. The Canterbury meeting sought to move beyond dialogue to ideas for specific joint faith-development initiatives and programs. The Millennium Development Goals -- which represent a new global determination to mobilize energy, passion, and resources to fulfill tangible, measurable imperatives for human health and well-being-served as a springboard for discussion and provide a framework for future partnerships. The goals are straightforward: eradicate extreme poverty and hunger; achieve universal primary education; promote gender equality and empower women; reduce child mortality; improve maternal health; combat HIV/AIDS, malaria, and other diseases; ensure environmental sustainability; and develop a global partnership for development. Global leaders and institutions such as the World Bank are committed to judging their performance against these goals.